Chemical Composition and Nutritive Value of Khejri (Prosopis Cineraria) Tree Leaves - Bhandari, D S; Govil, H N; Hussain, A (Annals of Arid Zone, 2016)
A digestibility trial was conducted on five Chokla rams with Khejri leaves (Prosopia cineraria). The animals showed loss of weight during the trial period. The dry matter consumption was 2.10 kg per 100 kg body weight. The digestibility coefficient of crude protein, ether extract, crude fibre, N.F.E. were found to be 31.65, 34.82, 50.90 and 41.13 respectively. The loss of weight might be due to poor utilization of protein and energy.